Patient-reported outcome measures to deliver patient and family-centered care in pediatrics: the ball is now in our court - Bele, Sumedh; Santana, Maria J. (Frontiers in Health Services, 2025)
Patient-reported Outcome Measures (PROMs) are self-reported questionnaires that are used to deliver patient and family-centered care, but their use in routine pediatric clinical care remains limited. The American Institute of Medicine (IOM) recommends patient-centered care to achieve high quality health care delivery and PROMs can be used in routine pediatric clinical care to support six critical dimensions of patient-centered care endorsed by the IOM. The growing evidence including our systematic review of pediatric PROMs, shows that incorporating PROMs into routine pediatric clinical practice significantly enhances the quality of care and has a positive impact on Health-related Quality of Life (HRQL) among children and youth. Thus, we are sharing our perspectives on the current evidence, emphasizing the need for using PROMs in routine pediatric clinical care and proposing strategies for pediatric implementation.